Proceedings of the Scientific-Practical Conference "Research and Development - 2016" - Anisimov, K. V.; Dub, A. V.; Kolpakov, S. K.; Lisitsa, A. V.; Petrov, A. N.; Polukarov, V. P.; Popel, O. S.; Vinokurov, V. A. (Springer International Publishing : Imprint: Springer, 2018)
This book is open access under a CC BY 4.0 license. It relates to the III Annual Conference hosted by the Russian Federal Ministry of Education and Science in December 2016. This event has summarized, analyzed and discussed the interim results, academic outputs and scientific achievements of the Russian Federal Targeted Programme for Research and Development in priority areas of development of the Russian Scientific and Technological Complex for 2014-2020. It contains 75 selected papers from 6 areas considered priority by the Federal programme: computer science, ecology & environment sciences; energy and energy efficiency; life sciences; nanoscience & nanotechnology; and transport & communications. The chapters report the results of the 3-years research projects supported by the Programme and finalized in 2016.